2a+4=-(9-a)

Simple and best practice solution for 2a+4=-(9-a) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2a+4=-(9-a) equation:


Simplifying
2a + 4 = -1(9 + -1a)

Reorder the terms:
4 + 2a = -1(9 + -1a)
4 + 2a = (9 * -1 + -1a * -1)
4 + 2a = (-9 + 1a)

Solving
4 + 2a = -9 + 1a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-1a' to each side of the equation.
4 + 2a + -1a = -9 + 1a + -1a

Combine like terms: 2a + -1a = 1a
4 + 1a = -9 + 1a + -1a

Combine like terms: 1a + -1a = 0
4 + 1a = -9 + 0
4 + 1a = -9

Add '-4' to each side of the equation.
4 + -4 + 1a = -9 + -4

Combine like terms: 4 + -4 = 0
0 + 1a = -9 + -4
1a = -9 + -4

Combine like terms: -9 + -4 = -13
1a = -13

Divide each side by '1'.
a = -13

Simplifying
a = -13

See similar equations:

| 2.4x-5=2(2x+1) | | y=(2X-1)*(3X+2) | | 2(-1)+5y=3 | | 13-7x=-(5-11x) | | 13-7x=5-11x | | 25=5(a-7) | | 5v-18=10v-53 | | 3(-5x-17)=3 | | 2(4y)-y=-1 | | 8-3=2(x+1) | | B=3/4(21-b) | | (n+7)(11n-2)=18n(2n+1) | | A=21-b | | 4/3(-5.25) | | f(4)=2.0x^2+7.6x^4+5.0 | | f(x)=2.0x^2+7.6x^4+5.0 | | F=5(10)+18 | | 9w+(-31)= | | 11n^2+21n-14=0 | | -9/5x=27 | | q=m*c*changeT | | F=5(4)+18 | | F=5(2)+18 | | X+5a=29+ax-6a | | 2n=-28n-3 | | V=XLT | | 2x-x+112=16x+112 | | 3/e=3/4 | | 5n-6=18 | | 2y-3+y+6=12 | | F=5(3)+11 | | F=5(5)+11 |

Equations solver categories